An Approch For Development Of Oral Sustained Release Suspension - SOMPUR C.K; R.C.DOIJAD; S.M. PATIL; A.P.MASKE (International Journal of Pharma and Bio Sciences, 2011)
The scenario of pharmaceutical drug delivery is rapidly changing; conventional dosage forms are being replaced by new drug delivery system. One such drug delivery is sustained or controlled release drug delivery system the primary objective of sustained release drug delivery system is to ensure safety, improve the efficiency of drug, and also reduces the dose frequency, which also ultimately results in patient compliance. An oral pharmaceutical suspension has been one of the most favorable dosage forms for pediatric and geriatric patients or patients unable to tolerate solid dosage forms. The liquid form is preferred because of the ease of swallowing and flexibility in the administration of doses. More therapeutic and commercial advantages are as high patient compliance, reduction in side effects and improvement of bioavailability could be expected by incorporating a function of sustained drug release into the suspension. Therefore it is desirable to develop, well formulated sustained release suspension.